2023
DOI: 10.1007/s11356-023-29631-1
|View full text |Cite
|
Sign up to set email alerts
|

Indoor environment in relation to recurrent childhood asthma in Yancheng, China: a hospital-based case-control study

Baoping Zhang,
Zhibin Xia,
Xu Jiang
et al.

Abstract: Background:This investigation explored the association between indoor environmental factors and childhood asthma in Yancheng, China. Methods:Asthma case (201 children with recurrent asthma) and control cohorts (242 healthy subjects) were recruited from a Traditional Chinese Medical (TCM) Hospital in Yancheng city, based on the results of an ISAAC questionnaire. Questionnaires regarding environmental risk factors were completed by the child's primary caregivers. To compare data on environmental VOCs and formald… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…al reported that symptoms such as cough, burning eyes and nasal, wheezing, throat and eye irritation, asthma, etc. had high prevalence among healthcare workers exposed to formaldehyde 19 , 38 40 . Zhai et.…”
Section: Discussionmentioning
confidence: 99%
“…al reported that symptoms such as cough, burning eyes and nasal, wheezing, throat and eye irritation, asthma, etc. had high prevalence among healthcare workers exposed to formaldehyde 19 , 38 40 . Zhai et.…”
Section: Discussionmentioning
confidence: 99%